Shift work - change from semi-continuous to continuous system - Silva, Isabel Maria Soares da (2018)
Purpose The purpose of this paper is to understand workers' resistance toward change from a semi-continuous (SCW) to a continuous shift work system (CW), especially focusing the perspective of change and its impact on workers' personal lives.Design/methodology/approach A case study was conducted at a Portuguese steel plant. A questionnaire was administered to 98 shift workers of the two systems, three focus groups (FG) each with ten CW workers, and three interviews with their managers.Findings The results of the FG and the interviews indicate the loss of days off during weekends as the main drawback of this change, leading to work schedule dissatisfaction. The consequences of the change focused on social and family life. For the CW workers, the conciliation between working hours and life outside the company were the only predictors of satisfaction with work schedule.Research limitations/implications The cross-sectional design is one of the main limitations, as well the use of only one organization in the study suggests future replication. Organizations need to consider the aspects of family and social life in the management of working hours.Originality/value Globally, this case study highlights the importance of family and social aspects in the adjustment process to working hours, especially when these involve performing work on the weekends, such as shift work.